Importance of anatomical knowledge in Eagle Syndrome: report on dry skulls (Research, Society and Development, 2020)
The styloid process is a bony and pointed projection that originates in the temporal bone and its standard length varies from 25 to 30 mm. When this length is exceeded, this bone accident is considered elongated, which associated with specific symptoms may indicate the diagnosis of Eagle syndrome. This report was an anatomical, observational finding, performed from osteotechnics on dry adult skulls, owned by the Human Anatomy laboratory at the Federal University of Paraná - Campus Toledo. The findings were measured with a caliper nove. Among twelve human bones analyzed, two had an elongated styloid process that were 45 mm long on the right side and 43 mm on the left side in skull 1 and 41 mm long on the left side and 39mm on the right side in skull 2. Thus, the length measurements of the styloid apophyses found are larger than the average of the sizes reported in the literature, which suggests that this anomalous styloid process would be compressing adjacent structures and causing clinical symptoms compatible with Eagle's Syndrome. Knowledge about the pathology, as well as its clinical manifestations, may favor the suspicion of the disease by medical professionals.